A double-blind placebo controlled trial into the impacts of HMB supplementation and exercise on free-living muscle protein synthesis, muscle mass and function, in older adults. Issue 5 (October 2019) - Din, U.S.U.; Brook, M.S.; Selby, A.; Quinlan, J.; Boereboom, C.; Abdulla, H.; Franchi, M.; Narici, M.V.; Phillips, B.E.; Williams, J.W.; Rathmacher, J.A.; Wilkinson, D.J.; et al.
Summary: Age-related sarcopenia and dynapenia are associated with frailty and metabolic diseases. Resistance exercise training (RET) adjuvant to evidence-based nutritional intervention(s) have been shown as mitigating strategies. Given that β-hydroxy-β-methyl-butyrate (HMB) supplementation during RET improves lean body mass in younger humans, and that we have shown that HMB acutely stimulates muscle protein synthesis (MPS) and inhibits breakdown; we hypothesized that chronic supplementation of HMB free acid (HMB-FA) would enhance MPS and muscle mass/function in response to RET in older people. We recruited 16 healthy older men (Placebo (PLA): 68.5 ± 1.0 y, HMB-FA: 67.8 ± 1.15 y) for a randomised double-blind-placebo controlled trial (HMB-FA 3 × 1 g/day vs. PLA) involving a 6-week unilateral progressive RET regime (6 × 8 repetitions, 75% 1-RM, 3 · wk −1 ). Deuterium oxide (D2 O) dosing was performed over the first two weeks (0–2 wk) and last two weeks (4–6 wk) with bilateral vastus lateralis (VL) biopsies at 0–2 and 4–6 wk (each time 75 ± 2 min after a single bout of resistance exercise (RE)) for quantification of early and later MPS responses and post-RE myogenic gene expression. Thigh lean mass (TLM) was measured by DXA, VL thickness and architecture (fibre length and pennation angle) by ultrasound at 0/3/6 wk, and strength by knee extensor 1-RM testing and MVC by isokinetic dynamometry (approx. every 10 days). RET induced strength increases (1-RM) in the exercised leg of both groups (398 ± 22N to 499 ± 30N HMB-FA vs. 396 ± 29N to 510 ± 43N PLA (both P < 0.05)). In addition, maximal voluntary contraction (MVC) also increased (179 ± 12 Nm to 203 ± 12 Nm HMB-FA vs. 185 ± 10 Nm to 217 ± 11 Nm PLA (both P < 0.05); with no group differences. VL muscle thickness increased significantly in the exercised leg in both groups, with no group differences. TLM (by DXA) rose to significance only in the HMB-FA group (by 5.8%–5734 ± 245 g p = 0.015 vs. 3.0% to 5644 ± 323 g P = 0.06 in PLA). MPS remained unchanged in the untrained legs (UT) 0–2 weeks being 1.06 ± 0.08%.d −1 (HMB-FA) and 1.14 ± 0.09%.d −1 (PLA), the trained legs (T) exhibited increased MPS in the HMB-FA group only at 0–2-weeks (1.39 ± 0.10%.d −1, P < 0.05) compared with UT: but was not different at 4–6-weeks: 1.26 ± 0.05%.d −1 . However, there were no significant differences in MPS between the HMB-FA and PLA groups at any given time point and no significant treatment interaction observed. We also observed significant inductions of c-Myc gene expression following each acute RE bout, with no group differences. Further, there were no changes in any other muscle atrophy/hypertrophy or myogenic transcription factor genes we measured. RET with adjuvant HMB-FA supplements in free-living healthy older men did not enhance muscle strength or mass greater than that of RET alone (PLA). That said, only HMB-FA increased TLM, supported by early increases in chronic MPS. As such, chronic HMB-FA supplementation may result in long term benefits in older males, however longer and larger studies may be needed to fully determine the potential effects of HMB-FA supplementation; translating to any functional benefit.